Parasite assemblages of Cape horse mackerel (Trachurus capensis Castelnau, 1861) from the northern and southern Benguela - Le Roux, Jessica Louise (Department of Biological Sciences, 2014)
A survey of parasites infecting Cape horse mackerel, Trachurus capensis Castelnau, 1861, from both the southern and northern Benguela ecosystems was conducted to test the hypothesis of discrete stocks in each subsystem. One hundred and twenty five T. capensis of two size classes were collected off the coasts of South Africa and Namibia and their bodies and organs were examined for parasitic infections. Differences in parasite assemblages between smaller and larger T. capensis within each subsystem, between T. capensis of each size class from the two subsystems, and between larger fish collected in different seasons within the southern Benguela, were assessed. A total of twenty-nine parasite species were found infecting T. capensis. Ten of these were identified to species level (Ceratomyxa australis, Davisia donecae, Ectenurus lepidus, Gastrocotyle trachuri, Goussia cruciata, Lernanthropus trachuri, Nybelinia lingualis, Rhadinorhynchus cadenati, Scolex pleronectis and Tergestia laticollis), three to genus level (Anisakis sp., Caligus sp. and Kudoa sp.). Significant spatial differences in T. capensis parasites were observed, with larger fish differing in infection intensity and abundance of Anisakis sp. and infection intensity of L. trachuri. Significant spatial variation in parasites was also observed in smaller fish, which differed in Anisakis sp. abundance, L. trachuri infection intensity and abundance, G. trachuri abundance and G. cruciata infection intensity and abundance. Significant fish size effects on T. capensis parasites were also observed in both subsystems. Anisakis sp. infection intensity and abundance and G. cruciata abundance differed significantly between larger and smaller fish from the southern Benguela. Larger and smaller fish from the northern Benguela differed in G. cruciata infection intensity and abundance, G. trachuri abundance and L. trachuri abundance. No seasonal differences in parasites of larger T. capensis from the southern Benguela were observed. By using a discriminant function analysis parasite abundance data correctly assigned 92% of larger fish and 96% of smaller fish to their respective southern and northern Benguela sub-populations or stocks. These results show that analyses of parasites can be used to infer population structure and support the hypothesis of distinct T. capensis stocks in the northern and southern Benguela subsystems.